Discovery of Time-Series Motif from Multi-Dimensional Data Based on MDL Principle. - Tanaka, Yoshiki
Recently, the research on efficient extraction of previously unknown, frequently appearing patterns in a time-series data has received much attention. These patterns are called lsquomotifsrsquo. Motifs are useful for various time-series data mining tasks. In this paper, we propose a motif discovery algorithm to extract a motif that represents a characteristic pattern of the given data based on Minimum Description Length (MDL) principle. In addition, the algorithm can extract motifs from multi-dimensional time-series data by using Principal Component Analysis (PCA). In experimental evaluation, we show the efficiency of the motif discovery algorithm, and the usefulness of extracted motifs to various data mining tasks.
Keywords: Time-series motifs; Multi-dimensional time-series data; PCA; MDL principle